Hydrolysis of semi‐industrial aqueous extracted xylan from birch (Betula pendula) employing commercial catalysts: kinetics and modelling. Issue 1 (21st September 2021) - Lu, Xiaojia; Junghans, Paula; Wärnå, Johan; Hilpmann, Gerd; Lange, Rüdiger; Trajano, Heather; Eränen, Kari; Estel, Lionel; Leveneur, Sebastien; Grénman, Henrik
Abstract: BACKGROUND: Acidic hydrolysis of a birch ( Betula pendula ) xylan produced by a novel semi‐industrial‐scale aqueous‐based and highly sustainable method was studied in a batch reactor. Five commercial acidic heterogeneous catalysts were screened and significant differences in their performance were observed. Dowex 50WX2‐100 was selected for further studies and the influence of the reaction parameters, including stirring speed, pH (0.5–1.5), temperature (115–145 °C) and catalyst particle size (50–400 mesh) were studied. The goal was to maximize xylose yield by balancing between the kinetics of hydrolysis and the undesired degradation of monosaccharides. RESULTS: The results show that the maximum achieved yield of xylose was 76%, but higher yields were hindered by the consecutive dehydration of sugars. It was also observed that the hydrolysis and dehydration reactions do not follow the same dependence on the experimental parameters, which leaves room for optimization of the yield. A kinetic model was developed based on the data, which takes into account the consecutive reaction pathway and the influence of the experimental conditions, and a very good fit of the model to the experimental data was achieved. An activation energy of 119 and 88 kJ mol –1 was obtained for the hydrolysis and dehydration steps, respectively. CONCLUSION: Hydrolysis results of this novel, well‐characterized hemicellulose extract have not been published previously, and they contribute significantly to the understanding of the hydrolysis and dehydration of real feedstock, instead of highly purified and typically very deacetylated model compounds with different characteristics and behaviour in hydrolysis. © 2021 The Authors. Journal of Chemical Technology and Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry (SCI).